Structure Changes in the Surface Layers of Ti-6Al-4V Titanium Alloy under Electron Beam Treatment; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Sinyakova E. Elena; Panin A. V. Alexey Viktorovich; Perevalova O. Olga; Kazachenok M. Marina; Ivanov Yu. Yurii; Kalashnikov M. P. Mark Petrovich (2017, 2017)
Title screen